2021
DOI: 10.3390/children8050359
|View full text |Cite
|
Sign up to set email alerts
|

Subtalar Arthroereisis for Flexible Flatfoot in Children—Clinical, Radiographic and Pedobarographic Outcome Comparing Three Different Methods

Abstract: Subtalar arthroereises (STA) is a minimally invasive and reversible surgery to correct symptomatic flexible flatfoot (FFF) in children. Various techniques were described either applying expandable sinus tarsi implants or lateral calcaneus stop screws. Studies comparing the outcome of STA with different devices are rare. This retrospective single-center cohort study analyzes the results of STA using three different implants. 113 STA were performed in 73 consecutive patients (28 females). Mean age at surgery was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(52 citation statements)
references
References 38 publications
4
46
1
1
Order By: Relevance
“…Similar results have already been published, and arthroeresis has been found to yield improved gait pattern and less pain [13][14][15][16]. In addition, the frequency of complications described in the present study is similar to that reported previously on subtalar titanium implants [14,17].…”
Section: Discussionsupporting
confidence: 91%
“…Similar results have already been published, and arthroeresis has been found to yield improved gait pattern and less pain [13][14][15][16]. In addition, the frequency of complications described in the present study is similar to that reported previously on subtalar titanium implants [14,17].…”
Section: Discussionsupporting
confidence: 91%
“…As well, De Pellegrin et al [11] reported that there was significant improvement of pain at 3 months postoperatively compared to preoperative pain score.…”
Section: Discussionmentioning
confidence: 87%
“…As well, De Pellegrin et al [11] reported that the Costa-Bartani angle was measured at 146° ± 7° and 129° ± 5°, respectively, while the talar inclination angle was measured at 43° ± 8°, and 25° ± 6°, respectively [p 0.001]. The calcaneal pitch was measured at 11° ± 6°, and 14° ± 5°, respectively.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Almost all authors concentrate on objectives aspects of the procedure [ 1 , 13 16 ]. The study itself is based on a wide spectrum of objective clinical, radiological, podoscopic and pedobarographic measurements, together with subjective observations based on a specifically-designed foot health survey completed by the patients.…”
Section: Introductionmentioning
confidence: 99%